HEART AND LUNG FAILURE, TRANSPLANTOLOGYThe relationship between late gadolinium enhancement imaging and myocardial biopsy in the evaluation of chronic heart failure patients with suspected myocarditis - Nowak, Jolanta; Wasilewski, Jarosław; Reichman-Warmusz, Edyta; Spinczyk, Beata; Głowacki, Jan; Miszalski-Jamka, Karol; Szyguła-Jurkiewicz, Bożena; Tajstra, Mateusz; Badziński, Arkadiusz; Wojnicz, Romuald; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Aim: The aim of this study was to assess the relationship between late gadolinium-enhanced (LGE) cardiovascular magnetic resonance (CMR) and immunohistochemical markers of inflammation in patients with heart failure and a reduced ejection fraction (HFrEF). Material and methods : Endomyocardial biopsy and CMR were performed in 38 consecutive patients (24 males, average age 43.2 ± 6.9 years, New York Heart Association [NYHA] class II) with HFrEF and suspected myocarditis. The immunohistochemical evaluation was done by the En-Vision system using DAKO monoclonal antibodies. The presence of > 14 infiltrating cells together with myocardial damage and ≥ 2 + up-regulation of HLA class II was considered diagnostic for myocarditis. The results of LGE were compared with the immunohistochemical markers of inflammation. All patients underwent coronary angiography. Results: Twelve out of 38 (31.6%) patients met the immunohistological criteria for the diagnosis of myocarditis. Late gadolinium enhancement was present in 23 of 38 (60.5%) patients, mostly at the interventricular septum. No correlation was found between LGE and immunohistochemistry results (Kendall’s tau; r = 0.21, p = 0.09). Conclusions: Our study revealed no significant relationship between LGE cardiovascular magnetic resonance imaging and immunohistochemical markers of inflammation in patients with HFrEF.